Kinematical aspects dliding technique in 500-m speed skaters: From start to seven strokes - Ryu, J. K.; Kim, Y. S.; Hong, S. H. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to assess the consistency of the gliding and push-off motion for single leg skating from the first to fourteenth steps. We hypothesized that: 1) there would be no difference in stroke trajectory, step rate, and cycle rate between the left and right steps of gliding; and 2) there would be a difference in the resultant velocity of toe push-off and the horizontal velocity of the center of mass after six step push-offs.